2013
DOI: 10.4018/ijmbl.2013100103
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality and Mobile Learning

Abstract: In this paper, the authors examine the state of the art in augmented reality (AR) for mobile learning. Previous work in the field of mobile learning has included AR as a component of a wider toolkit but little has been done to discuss the phenomenon in detail or to examine in a balanced fashion its potential for learning, identifying both positive and negative aspects. The authors seek to provide a working definition of AR and to examine how it can be embedded within situated learning in outdoor settings. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(110 citation statements)
references
References 53 publications
2
104
0
4
Order By: Relevance
“…In 2013, FitzGerald et al [17] published a review on AR in the context of mobile learning where they analyzed six mobile learning systems that utilized AR as a key component. Their comparison taxonomy featured six variables, mostly focusing on non-technical aspects: device/technology, mode of interaction/learning design, method of sensory feedback, personal/shared experience, fixed/static or portable experience, and learning activities.…”
Section: Related Workmentioning
confidence: 99%
“…In 2013, FitzGerald et al [17] published a review on AR in the context of mobile learning where they analyzed six mobile learning systems that utilized AR as a key component. Their comparison taxonomy featured six variables, mostly focusing on non-technical aspects: device/technology, mode of interaction/learning design, method of sensory feedback, personal/shared experience, fixed/static or portable experience, and learning activities.…”
Section: Related Workmentioning
confidence: 99%
“…Many authors [3][9] [10] have identified learning as an interesting and promising field in which AR could be applied. [3] writes that AR systems could "help learners develop skills and knowledge that can be learned in other technology environments but in a more effective way" and as [9] writes "AR can enhance our situated learning by augmenting our realties more effectively". According to several, such as [10] [11] [12], AR increases the effectiveness of and motivation for learning.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its potential and the availability of the equipment needed for an AR system, it has been used in different contexts, such as medicine, military, entertainment, training, tourism, social networking, industrial applications, cultural heritage etc. Mobile AR has been used in different projects, a wide taxonomy of which is available in FitzGerald et al (2013) work. Furthermore, the authors stress the educational potential of AR; they mention a series of studies that empirically indicate the efficiency of AR in • Promoting engagement and motivation (Klopfer & Squire, 2008;Luckin & Stanton Fraser, 2011); • Improving memorability, engagement (Luckin & Stanton Fraser, 2011) and motivation (Di Serio et al 2012); • Improving spatial skills (Martin-Gutierrez et al 2011;Schmalstieg & Wagner, 2007); • Supporting collaborative problem solving, (Cook 2010).…”
mentioning
confidence: 99%